Multimodal Analgesia Approach in Acute Low Back Pain Management: A Phase III Study of a Novel Analgesic Combination of Etoricoxib/Tramadol - Zuqui-Ramírez, Miguel A.; Belalcazar-López, Victor M.; Urenda-Quezada, Adelfia; González-Rebatu y González, Alejandro; Sander-Padilla, José G.; Lugo-Sánchez, Laura A.; Rodríguez-Vázquez, Ileana C.; Rios-Brito, Kevin F.; Arguedas-Núñez, María M.; Canales-Vázquez, Emmanuel; González-Canudas, Jorge (Pain and therapy, 2024)
Introduction Pain and disability management are crucial for a speedy recovery. Combining analgesics with different mechanisms of action provides greater pain relief with lower doses, promoting efficient multimodal analgesia. This study evaluated the efficacy and safety between two fixed-dose combinations (FDC): etoricoxib/tramadol compared to paracetamol/tramadol for the management of acute low back pain (LBP) in a 7-day treatment. Methods We conducted a phase IIIb, prospective, randomized, and multicenter study in patients with acute LBP treated with etoricoxib 90 mg/tramadol 50 mg (one packet of granules diluted in 100 ml of water, once a day [QD], for 7 days) or paracetamol 975 mg/tramadol 112.5 mg (one tablet of 325 mg/37.5 mg, three times a day [TID], for 7 days) to assess the efficacy (in terms of pain and disability improvement) and safety. Results One hundred and twenty-four patients were randomized to receive either etoricoxib/tramadol QD ( n = 61) or paracetamol/tramadol TID ( n = 63). From the magnitude of change in pain evaluations, differences were observed between the treatment groups at 3 [ p = 0.054, CI 95% − 0.648 (− 0.010 to 1.306)] and 5 days ( p = 0.041). The proportion of patients with a 30% reduction in Visual Analogue Scale (VAS) score was statistically significant when comparing the treatment groups on the third day of follow-up [ p = 0.008, CI 95% 0.241 (0.061–0.421)]. An improvement in LBP’s disability to perform activities of daily routine (Oswestry and Roland–Morris questionnaires) was observed in both treatment groups. A total of 79 adverse events (AEs) (38 [48.1%] with etoricoxib/tramadol and 41 [51.9%] with paracetamol/tramadol) were reported. The most frequent AEs were nausea (17.7%) and dizziness (16.4%). Conclusions The results show the clinical benefits of etoricoxib/tramadol FDC, such as the sparing effect of tramadol dose per day, early therapeutic response rate compared with paracetamol/tramadol; which translates into faster pain relief, better adherence, less tramadol drug dependency, and a reduction of related AEs incidence. Trial registration ClinicalTrials.gov identifier, NCT04968158.